HUBUNGAN PEMAHAMAN TEORI TUMPENG TEDAK SITEN TERHADAP HASIL BELAJAR PRAKTIKUM SISWA SMK NEGERI 8 SURABAYA - Pangkratia Xavera Dua Hero; Susilowati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between students' understanding of Tumpeng Tedak Siten theory and their practical learning outcomes in the Special Dishes subject at SMK Negeri 8 Surabaya. The study is motivated by the importance of integrating theory and practice in vocational learning based on local culture, since Tumpeng Tedak Siten is studied not only as a culinary product but also as a learning medium containing philosophical, symbolic, and spiritual values within Javanese culture. A quantitative correlational design was employed involving 60 Culinary Arts students selected through purposive sampling. Data were collected using a Likert-scale questionnaire to measure theoretical understanding and documentation of practical scores to measure learning outcomes, then analyzed using Pearson Product Moment correlation with IBM SPSS 24. The results show that both instruments were valid and reliable (Cronbach's Alpha of 0.730 and 0.825), the data were normally distributed and linear, and there was a very strong, significant positive relationship between theoretical understanding and practical learning outcomes (r = 0.938; sig. = 0.000 < 0.05), with a coefficient of determination of 88%. These findings confirm that theoretical mastery is an essential prerequisite for successful practice, so learning strategies that optimally integrate theory and practice are needed to achieve more effective and meaningful learning outcomes.